Effectiveness of Education Using Videos and VCO Application Modules in Reducing ISPA Symptoms in Children - Nurwahidah Nurwahidah; Syaiful Syaiful; Aniharyati Aniharyati; Fitrah Abubakar; Masruroh Masruroh (International Journal of Social Service and Research, 2023)
Acute respiratory infections are one of the most common causes of death in children. Around four out of fifteen million estimated deaths are in children under 5 years of age ( Wiwin et al, 2020). ISPA is a disease that often occurs in developing countries and is one of the causes of patient visits to health centers (40%-60%) and hospitals (15%-30%). The five provinces with the highest ISPA are, NTT (41.7%), Papua (31.1%), Aceh (30.0%), NTB (28.3%), and East Java (28.3%). Based on the NTB Health Profile (2020) in 2019, ARI was the number one case in the category of the 10 most common diseases in NTB with the highest number of visits, namely 174,213 visits (NTB Health Office, 2018). Based on the results of the Indonesian Health Profile in 2020, the number of patient visits with ISPA in the NTB area was 182,204. Based on data from the 2020 Indonesian Health Profile, NTB is ranked 6th with the highest number of patient visits with ISPA in Indonesia. Quantitative research with a quasi-experimental approach with control group design. The sampling technique was consecutive sampling with 100 respondents. The results of the paired sample T test data analysis showed that the knowledge of the intervention group had ap value of 0.000 < 0.05 and the control group had ap value of 0.01 < 0.05. Then the skills of the intervention group obtained ap value of 0.000 < 0.05 and the control group obtained ap value of 0.05. These results show that Ha is accepted and H0 is rejected so it can be interpreted that there is an educational effect using videos and the VCO application module in reducing ARI symptoms in children.